Improvement of information support for formation of management reporting on the example of the activities of an energy company - M. N. Belousova; M. N. Oreshina (Управление)
The purpose of the study is to develop a system for generating management reporting on the production activities of an energy company on the SAP Business Objects Platform. To build a reporting system, the following tasks has been set and solved: the conceptual and datalogical models of the data warehouse were created, data areas have been selected from the general data model, the data warehouse has been designed and developed, universes for report groups have been created, a mechanism for integrating data with the data warehouse has been implemented.The paper analyses the information and technological infrastructure of an energy company as well as formulates the basic requirements for the system being created for generating reporting. Two main subsystems have been designed: data storage and integration. The process of implementing the designed subsystems in physical form has been described using the appropriate software products: SAP Hana, SAP Universe Designer, SAP Data Services, SAP Business Intelligence.Thanks to the configured system through the corporate data bus, a relatively simple data integration mechanism became possible. In its information and technological architecture, the company managed to simulate an acceptable data warehouse model and set up the appropriate data flows. A complex data warehouse model has been implemented, and a convenient platform for further data processing has been provided. A clear data integration scheme is configured using SAP Data Services, with the ability to scale and configure the data loading schedule. The developed system has been put into operation and is used by employees to make management decisions within the framework of their professional activities.